2016
DOI: 10.3389/fpsyg.2016.00593
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Intention Maintenance and Impaired Execution of Prospective Memory Responses in Schizophrenia: Evidence from an Event-based Prospective Memory Study

Abstract: Executive system dysfunction and impaired prospective memory (PM) are widely documented in schizophrenia. However, it is not yet clarified which components of PM function are impaired in this disorder. Two plausible target components are the maintenance of delayed intentions and the execution of PM responses. Furthermore, it is debated whether the impaired performance on frequently used executive tasks is associated with deficit in PM functions. The aim of our study was twofold. First, we aimed to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…In the PM execution phase, the typical instruction group showed stronger activation in the precentral gyrus (BA 6) and middle frontal gyrus (BA 8) than the implementation intention group. The precentral gyrus (BA 6) is located close to the pre‐supplementary motor area (pre‐SMA) and the supplementary motor area (Demeter et al, ) and it functions together with somatosensory areas to implement the PM actions. So, in this phase the PM intention transferred from an abstract level to a concrete and action‐related level (Cona et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the PM execution phase, the typical instruction group showed stronger activation in the precentral gyrus (BA 6) and middle frontal gyrus (BA 8) than the implementation intention group. The precentral gyrus (BA 6) is located close to the pre‐supplementary motor area (pre‐SMA) and the supplementary motor area (Demeter et al, ) and it functions together with somatosensory areas to implement the PM actions. So, in this phase the PM intention transferred from an abstract level to a concrete and action‐related level (Cona et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to event-based PM, deficit in time-based PM persisted. Demeter et al, 2016 Chronic schizophrenia patients (n=20) and matched healthy controls (n=20)…”
Section: Cheung Et Al 2015mentioning
confidence: 99%
“…Since these two reviews, a number of studies that examined PM impairments in individuals with schizophrenia have been published. Three studies Au et al, 2016;Demeter et al, 2016) found severe PM impairments in individuals with chronic schizophrenia. Three studies (Cheung et al, 2015;Liu et al, 2017;Lui et al, 2015) showed that first-episode and even first-episode medication-naïve individuals with schizophrenia demonstrated PM impairments.…”
Section: Pm Impairments In Individuals With Schizophrenia and Relatedmentioning
confidence: 99%
“…There are a number of endophenotypes, and cognitive endophenotypes have been extensively studied. So far, some research has shown that the impairment of PM exists within schizophrenia patients, regardless of chronic,47,6063 first-episode, or even first-episode drug-naive status,6466 and meta-analyses and systematic reviews have been conducted 49,67. In this study, it was found that the non-psychotic first-degree relatives of patients with schizophrenia had defects in their prospective memory.…”
Section: Discussionmentioning
confidence: 63%